(untitled) (The Batuk, 2021)
In her novel Fire on the Mountain, Anita Desai, by making her characters burn the images related to the ill and superstitious law of the anthropocentric world, intends to revere the natural world, which for her possesses healing capacity to revive the dying identity. Nanda Kaul, the protagonist and her great-granddaughter, finds pleasure with nothing else but with the barrenness, stillness, calmness and voice of silent breeze and music of nature itself. The fresh air of the quiet breeze in the naturally painted house wins the heart of the protagonist over the stale air of the electric fan in the artificially painted house. By utilizing theoretical ideas of ecofeminism in communication with deep ecology, the article concludes that the proper tribute to nature is possible when hierarchies between human and non-human blur and biocentric world view exists.